(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper aims to explore the role of digital HRM in enhancing organizational performance through innovation. The paper begins by defining what digital HRM is and how it differs from traditional HR practices. It then delves into the various ways in which digital HRM can contribute to organizational performance, such as through improving employee engagement, facilitating knowledge sharing, and enabling real-time data analysis. The paper also highlights some of the challenges associated with implementing digital HRM, including issues related to data privacy and security, resistance from employees who are not tech-savvy, and a lack of awareness among senior management about the benefits of adopting these practices